How to examine a wolverine : more tales from the accidental veterinarian - Schott, Philipp (ECW, 2021)
"Crammed with useful info, funny recollections, heartfelt anecdotes, and lots of cute furry creatures, a collection for all animal lovers! This collection of over 60 stories and essays, drawn from Dr. Schott's 30 years in small animal practice, covers an astonishing breadth of experiences, emotions, and species. Schott has tales of creatures ranging from tiny honeybees to massive Burmese pythons, although the emphasis is on dogs and cats and the interesting, often quirky, people who love them. He also doles out advice on current topics such as CBD oil, raw diets, and COVID-19, as well as the mysteries of catnip, dog flatulence, and duck erectile dysfunction. Schott's candor gives the reader a behind-the-scenes look at a profession that is much admired but often misunderstood. What is it really like to be a veterinarian? More to the point, what is it really like to be a veterinarian when confused pet parents call at 2:00 a.m.? Or when your patient bolts for the road? Or when you're asked to spay a dog on a resort's kitchen table? Readers will also learn how to make a sheep sit on its bum and, yes, how to examine a wolverine."--